Vedic Astrology and Its Perceived Impact on Management Decision Making - Sharma, Sushil Prasad; Bhandari, Suraj (Nepalese Journal of Insurance and Social Security, 2024)
Purpose: Planned Behavior Theory was utilized to investigate the perceived influence of astrology on the management decision making. This paper attempted to study the Vedic Astrology and how such astrological perspective signifies the management decision making.Design/Methodology/Approach: Structured Questionnaire was used and 103 valid responses were collected out of 130 distributed. Survey was conducted from different age group with different education background. Descriptive statistics were calculated and to measure perceptual impact, rank was computed. For more descriptive support, different cross tabulation was computed.Findings and Conclusion: The study concludes that every individual believes in astrology in different forms some believe it in the form of palmistry, some believe in birth chart “Kundali”, some believe in numerology and so on. Study also reveals that there is no any impact of gender, age and education on believe in astrology or it can be said that, the choice behind astrology in any form is independent of gender, age and education. Similarly, gender and education have no any impact towards the following the fortune teller or astrology or in any other form.Implications: This paper highlights astrological practices and culture especially in case of fortune teller and there were no any discussion regarding to specified astrological methods. Further, researcher may broaden the finding by incorporating particular astrology technique or methods like palmistry, numerology, and broaden aspect of Kundali.